Strategi Pemberdayaan UMKM Berbasis Potensi Lokal Desa Cisaruni Kecamatan Padakembang Kabupaten Tasikmalaya - Asyah, Yesi Nur; Maulana, Irfan; Maulidanti, Yuli (Jurnal ADMINISTRATOR, 2025)
This research is titled "Strategies for Empowering UMKM Based on Local Potential in Cisaruni Village, Padakembang District, Tasikmalaya Regency." The background for choosing this title is due to the discovery of issues indicating that community empowerment through Micro, Small, and Medium Enterprises (MSMEs) in Cisaruni Village, Padakembang District, Tasikmalaya Regency is not yet optimal. The theory used in this research is the stages of empowerment according to Mardikanto and Soebianto (2013:114). This research uses qualitative methods. The data collection techniques used are interviews, observations, and documentation studies. Based on the research and discussion results, it can be concluded that the community empowerment strategy through Micro, Small, and Medium Enterprises (MSMEs) in Cisaruni Village, Padakembang District, Tasikmalaya Regency is not yet optimal